Relações coesivas e estruturais: um estudo de conjunções em córpus paralelo e comparável no par linguístico inglês - português brasileiro - Leonardo Pereira Nunes (2014)
This dissertation reports a study of cohesive and structural conjunctions in a parallel and comparable corpus. Drawing on Corpus Linguistics (Granger 2003, Neumann 2005, 2008, Jesus 2008, Halliday & Webster 2009), Systemic-Functional Linguistics (Martin & Rose 2003, Halliday & Matthiessen 2004, 2014), Descriptive Translation Studies and Rhetorical Structure Theory (Mann & Thompson 1987, Matthiessen 2004), it examines patterns in the use of conjunctions regarding a) frequency of occurrence, b) meaning making within CONJUNCTION and CLAUSE COMPLEXING, c) interdependency relations, d) rhetorical relations and e) orientation towards field and/or tenor. Data was retrieved from Córpus de Língua Portuguesa em Tradução, a bidirectional parallel and comparable corpus in the English-Brazilian Portuguese language pair comprising samples of eight different text types: research article, political speech, science popularisation, fiction, instruction manual, tourism leaflet, review and educational website. First POS tagging was carried out with TreeTagger (Schmid, 1994) and word frequency and significance testing was performed in the R environment. The latter was conducted to test the impact of language typology and register variation on the frequency of conjunctions. The findings a) fully corroborated the hypothesis as to frequencies highly above the expected in argumentative texts (Neumann 2008) and b) partially corroborated the hypotheses as to frequencies highly above the expected in translated texts in both languages and in original and translated texts in Brazilian Portuguese (Vieira 1984, Blum-Kulka 1986). The results combining data from the comparable monolingual and comparable bilingual corpus also showed frequencies high above and down below expected in educational website texts. As a second step, samples of educational website texts were chosen and annotated for inquiries into lexicogrammar. They were also segmented for queries in semantics and in context. In the English texts, the results within lexicogrammar as to structural conjunctions showed common occurrence patterns a) in between main clauses and dependent clauses and non-occurrence patterns b) in dependent clause initials. In the Brazilian Portuguese texts, the results within semantics indicated common non-occurrence patterns as to the conjunction para construing purpose/desire/expectant meanings in hypotactic clauses. The results within semantics in the English texts showed common occurrence patterns as to and realizing local external conjunction relations. In such texts and in the Brazilian Portuguese texts data also showed common external and local relations realized both by cohesive and structural conjunctions. Finally, findings within context revealed that rhetorical relations realized by cohesive and structural conjunctions were oriented towards field and towards the expository rhetorical mode in all parallel and comparable texts.